Petovionske Nutrice in njihov potencialni vpliv na češčenje Marije - Visočnik, Julijana (Edinost in dialog, 2025)
The Nutrices, traditionally attributed a pre-Roman origin, are regarded as the most significant cult phenomenon in Poetovio. Their exceptional prominence is attested not only by the considerable number of monuments on which they appear – epigraphically, iconographically, or, in many cases, both – but also by the adoption of their cult by Italian settlers and its dissemination across all strata of society. Votive dedications identify dedicants ranging from members of the municipal elite to freedmen, slaves, and peregrini. Both ancient cults and contemporary philosophical thought significantly shaped the development of early Christian theology. In this context, it appears almost self-evident that the cult of the Nutrices, with its enduring presence and deeply rooted local significance, played a role in shaping the veneration of Mary as it gradually spread to this region. Nonetheless, the critical question remains: how can such an influence be substantiated?
Keywords: begginnings of Christianity; cult of Nutrices; češčenje Marije; kult Nutric; late antiquity and the early middle age; Petoviona (Poetovio); Poetiovio; pozna antika; veneration of Mary; začetki krščanstva; zgodnji srednji vek